Wireless power transfer using resonant inductive coupling - Design and implementation of an IPT system with one meter air gap in the region between near-range and mid-range - Nisshagen, Maria; Sjöstrand, Emma (My University, 2017)
Wireless power transfer (WPT) is the transmission of energy from a source to an electrical load over an air gap without using physical contact. One of the most common magnetic coupling WPT is the resonant inductive power transfer (IPT). It is a system which consist of at least one sending and one receiving coil which resonates to make the circuit appear resistive, thus decreasing the reactive power in the system and increasing the active power transfer. The IPT system can be classified to be either near-range or mid-range. Mid-range is when the distance between the coils is larger than the coil dimensions and near-range is when the distance between the coils is smaller than the coil dimension. The development of IPT technology has increased rapidly during the last couple of years, due to increased use of electrical vehicles and portable devices such as phones and laptops. Since resonant IPT is necessary to use where cables are impractical or inconvenient, the technology with larger distances between the coils is expected to be incorporated into society. However, more research needs to be done in this area, both in the aspect of improving the technology but also the risk of the electromagnetic fields to affect the human body negatively. The objective of this project is to wirelessly transfer power to a resistive load, located at a distance of one meter with a desired efficiency of at least 50 %. To fulfill the objective a two-coil model and a four-coil model were analyzed using a frequency of 200kHz. This was done by circuit calculations, simulations in COMSOL Multiphysics® and simulations in LTspice. It was decided that the two coil system was sufficient to use, thus it was the only model implemented in practice. The real system was tested with an output power of approximately 20 W by using loads between 5 and 20 . The achieved efficiency for a 10 load was 70 % in the simulations and 51 % in the real prototype. The difference was likely caused by a larger voltage drop in the wires than anticipated, a high quality factor, and due to the fact that the magnetic field was affected by surrounding metallic objects in the lab where the experiments were conducted.
Keywords: Elkraftteknik; Electric power engineering